INDICATORS OF QUALITY OF WORKING LIFE FOR PROFESSORS OF PUBLIC HIGHER EDUCATION INSTITUTIONS: A COMPARISON BETWEEN BRAZIL AND CANADA - Vilas Boas, Ana Alice; Morin, Estelle M. (Contextus - Revista Contemporânea de Economia e Gestão, 2016)
The main objective of this article is to assess the indicators of quality of working life (QWL) for academics and compare indicators of QWL in public universities in Brazil and Canada. The sample of this study consists of 205 professors of Minas Gerais and 269 from Quebec. Data were collected through an online questionnaire administered in February and March 2013.Three significant differences were found between the two samples: the meaning at work, affective commitment and continuance commitment. Brazilian professors seem to find more meaning in work than Canadian professors and they have more affective commitment with their institutions.